2017
DOI: 10.1007/s00414-017-1671-x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of advanced glycation end products (AGEs) in dentine: useful for age estimation?

Abstract: Ageing of the human organism results in the accumulation of modified molecules. Some of these molecular changes may be used for age estimation, as already shown for aspartic acid racemization (AAR). Another example for an accumulation of damaged molecules is advanced glycation end products (AGEs). We examined, (1) if the correlation between the concentration of AGEs (pentosidine) in root dentine and age is close enough to be used as basis for age estimation, and (2) if the combined analysis of AGEs and AAR in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 23 publications
0
22
0
5
Order By: Relevance
“…Besides being an important mechanism of the aging process, collagen glycation is relevant in pathologic conditions such as diabetes mellitus, due to the increased levels of glucose within tissues (Snedeker and Gautieri 2014). Recent research has suggested that dentin is also affected by AGE-mediated crosslinking, as increased levels of AGEs were found in older people (Shinno et al 2016; Greis et al 2018). However, the influence of these glycation-induced collagen modifications on oral streptococcal attachment onto surfaces and subsequent biofilm formation remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Besides being an important mechanism of the aging process, collagen glycation is relevant in pathologic conditions such as diabetes mellitus, due to the increased levels of glucose within tissues (Snedeker and Gautieri 2014). Recent research has suggested that dentin is also affected by AGE-mediated crosslinking, as increased levels of AGEs were found in older people (Shinno et al 2016; Greis et al 2018). However, the influence of these glycation-induced collagen modifications on oral streptococcal attachment onto surfaces and subsequent biofilm formation remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The PE/QE ratio showed moderate negative correlation with the chronological age. The correlation of the QE and PE level in vitreous were lower than teeth, cartilage, and bone samples 5,18 . The turnover rate of protein might be effect to the AGEs and pentosidine level in tissues.…”
Section: Discussionmentioning
confidence: 76%
“…The AGEs level contained in teeth were highly correlated with chronological age 5 . However, the teeth samples were difficult for sample preparation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…In general, aging is the gradual decline of physiological functions leading to age-dependent fitness loss, diseases and eventually mortality[99]. The process of aging is J o u r n a l P r e -p r o o f characterized, and likely influenced, by gradual alterations of biomolecules such as telomere repeat length, mitochondrial DNA mutations, accumulation of advanced glycation end products (AGEs), decline in signal joint T-cell receptor rearrangement excision circles (sjTRECs), aspartic acid racemization (AAR), epigenetic modifications and gene expression changes during the human lifespan[95,[100][101][102][103][104][105][106]. Among these age-associated biomarkers, epigenetic aging clocks represent the most accurate models for age prediction so far and have therefore attracted attention in the forensic field[107][108][109].…”
mentioning
confidence: 99%